Pengembangan Bahan Ajar Berbasis Kontekstual Pada Mata Pelajaran Akuntansi Perbankan dan Keuangan Mikro Kelas XI Perbankan SMK Negeri di Surabaya - Fitria, Syafi’ah Nur; Susanti, Susanti (Jurnal Pendidikan Akuntansi (JPAK), 2020)
Teaching materials are one of the components that are influential in achieving learning goals. Learning can be effective if the required components are available. However, in the subjects of banking accounting and microfinance is still limited. Therefore, the research purpose of this development is to produce teaching materials in the form of printed teaching books on contextual-based banking and microfinance accounting subjects for class XI vocational school with trial subjects of 20 learners from SMK Negeri 10 Surabaya. A 4-D model with define, design, and develop stages that is used as development procedure. That is done to produce an effective product. Descriptive qualitative and quantitative as technical analysis used. The results of the development of this teaching material showed the results of 83% of material experts, 84% from linguists, and 87% of graphicians. The interpretation criteria obtained from experts are very feasible while from the response of learners 86% with interpretation criteria are very understanding. Teaching materials made by looking at the results of these calculations can show that teaching. Based of the result of these calculations, the teaching materials can be effectively during the learning process.